Pengaruh Parameter Proses terhadap Kuat Tarik Produk Hasil 3d Printing Menggunakan Filamen ASA (Acrylonitrile Styrene Acrylate) - Wahyu Riyan Saputra; Zaldy Sirwansyah Suzen; Pristiansyah Pristiansyah (J-Proteksion, 2023)
3D Printing is an additive manufacturing technique that can be used to convert computer aided design (CAD) data and then print it by adding material layer by layer to form a 3D product. The FDM system is used for a 3D testing system because it is easy to use, the FDM system is also used as a rapid prototyping for making prototypes with polymer as the material. In this study the filament used was ASA (Acrylonitrile Styrene Acrylate) filament, the method used in this research to optimize process parameters was the Taguchi L9 OA method. The process parameters used are nozzle temperature, bed temperature, print speed, colling speed. This study aims to determine the tensile test stress strength of 3D printing product materials made from ASA (Acrylonitrile Styrene Acrylate) filaments with different parameters using the taguchi method and to find out how influential they are in printing with ASA filaments. The results showed that the optimal parameters for the tensile test using ASA (Acrylonitrile Styrene Acrylate) filaments were: nozzle temperature (240°C), bed temperature (50°C), print speed (60mm/s), colling speed (50°C) .